2007
DOI: 10.1029/2007gl029447
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal complexity of the Amazon flood measured from space

Abstract: [1] Floodplain processes are driven by water flows that seasonally change in direction and consist of a myriad of interacting streams of varying depth, velocity, source, sediment concentration and chemistry. Here we show, using spaceborne interferometric synthetic aperture radar (SAR) JERS-1 measurements, the first spatially dense hydraulic mapping of the passage of a flood wave through a large, topographically complex floodplain. We find that temporal changes in flood water heights (@h/@t) are more complex th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
149
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 27 publications
5
149
0
1
Order By: Relevance
“…they are either at one point or represent a full channel cross section), meaning that no information on water-surface area or two-dimensional patterns in water-surface slope is provided. However, synthetic aperture radar (SAR) interferometry work by Alsdorf et al (2007a) has shown that water flow is both spatially and temporally complex, requiring twodimensional, multi-temporal measurements to be captured sufficiently. This means that our current, operational remote sensing has limited capability with regard to an important component of the water surface (Alsdorf et al, 2007b).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…they are either at one point or represent a full channel cross section), meaning that no information on water-surface area or two-dimensional patterns in water-surface slope is provided. However, synthetic aperture radar (SAR) interferometry work by Alsdorf et al (2007a) has shown that water flow is both spatially and temporally complex, requiring twodimensional, multi-temporal measurements to be captured sufficiently. This means that our current, operational remote sensing has limited capability with regard to an important component of the water surface (Alsdorf et al, 2007b).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…The importance of these mechanisms, e.g. overtopping of topographical barriers and flow in floodplain channels, on the dynamics of floodplain inundation is crucial to the modelling of those dynamics in rural (Nicholas and Mitchell, 2003;Bates et al, 2006;Alsdorf et al, 2007) and urban areas (Schumann et al, 2011).…”
Section: Surface Water Connectivitymentioning
confidence: 99%
“…For instance, synthetic aperture radars (SARs) show very large capabilities to measure surface water extent. Studies in the Amazon basin [Smith and Alsdorf, 1998;Hess et al, 2003;Alsdorf et al, 2007b] or in the Congo prove the ability of SAR to delineate accurately the surface water in tropical forest environments with high spatial sampling intervals (∼100 m). However, large data volumes have limited these studies to a few samples of a few basins, preventing systematic, long-term assessments of inundation dynamics.…”
Section: Introductionmentioning
confidence: 99%